Pelatihan Budidaya Lebah tanpa Sengat di Desa Harapan Jaya Kecamatan Way Ratai Kabupaten Pesawaran - Mahfud Sidik; Indah Ayu Lestari; Lousanja Dira Sa’uddah; Ani Andri Yani; Priyambodo Priyambodo (Jurnal Mitrawarga, 2022)
Harapan Jaya Village, Way Ratai District, Pesawaran Regency is a village located at an altitude of 400 to 500 meters above sea level (masl), precisely on the southern slopes of Mount Pesawaran and directly adjacent to the protected block area of ​​Register 19 Forest. The majority of the population in this village are from the lower middle class and have quite difficult access from the center of the economy because of its location at an altitude. This training aims to increase the understanding of villagers about stingless beekeeping. The training began with a survey in February 2022 and followed up in May and June 2022. This training activity is an integrated part of the implementation of the Community Service Student Creativity Program (PKM-PM). The training was carried out at the Harapan Jaya Village Office and one of the residents' houses where logs beeThe method of implementing the training is through lectures, audio-visual media playback, questions and answers, and practice. Residents are trained to make bee logs, and choose a location for log placement of Trigona itama. An increase in public understanding is expected to have an impact on improving the people's economy, especially in the post-pandemic era.